Re-Assessing Red Blood Cell Storage - Linda M. Shecterle; Kathleen R. Terry JD; J. A. St. Cyr (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2015)
Numerous reports have surfaced over the past decade centering on the potential for complications when transfusing "new" versus "old" stored red blood cells (RBCs). The transfusion of whole blood and packed RBCs has been a standard medical treatment since Landsteiner in 1900 developed red cell ABO typing, leading to compatible transfusions from donor to recipient. Nearly fifteen million units of whole blood are donated in the United States each year by approximately eight million volunteer blood donors. These donor units are transfused to about four million recipients. Unfortunately, despite the great need and the generous contributions of volunteers, blood is always in short supply; and therefore, the need for donated blood continues. On any given day, approximately 35,000 units of blood are needed to treat surgical patients, accident victims, and patients who are anemic from leukemia, cancer, or other diseases.